Anatomical Study of Saphenous Nerve and Great Saphenous Vein Using a Peripheral Vein Illumination Device and Ultrasonography. Issue 4 (16th October 2019) - Ota, Yuki; Nakasa, Tomoyuki; Ikuta, Yasunari; Tsuyuguchi, Yusuke; Kanemitsu, Munekazu; Adachi, Nobuo
Category: Ankle, Basic Sciences/Biologics Introduction/Purpose: Usefulness of ultrasonographic guided saphenous nerve block is well known for perioperative pain management of foot and ankle surgery. However, in some cases it may be impossible to identify the saphenous nerve, especially women or obese patients, so successful rate of ultrasonographic guided saphenous nerve block was reported 70 to 80%. Previous reports demonstrated that the saphenous nerve is running adjacent to the greater saphenous vein, which suggests that the greater saphenous vein can be an indicator to identify the saphenous nerve. The purpose of this study was to examine anatomical relationship between the saphenous nerve and the greater saphenous vein which is depicted using the near-infrared (NIR) vascular imaging system, the Vein Viewer Flex®. Methods: Thirty legs as 15 healthy subjects (13 males, 2 females) were included in this study. Average age was 34.2 ± 3.2 years old. In a supine position, the knee joint was flexed 60 degrees with mild flexion, abduction, and external rotation of the hip joint, and the greater saphenous vein was depicted using the Vein Viewer Flex® on the skin of the lower extremity. The vein visualized as a green light was then marked using the skin marker. (Figure 1). After marking the greater saphenous vein, the greater saphenous vein and saphenous nerve were identified under ultrasonography at 5 cm distal from the medial knee joint space (Figure 2). The distance between the greater saphenous vein which was marked using the Vein Viewer Flex® and the saphenous nerve was measured in the ultrasonography images. The circumference of the leg (COL) was also measured. Results: The course of the greater saphenous vein could be depicted by the Vein Viewer Flex® in all cases, and it was confirmed by ultrasonography. It was confirmed that the saphenous nerve was located under the sartorius fascia and it was running posteromedially in parallel of the greater saphenous vein. The mean distance from the saphenous nerve and the greater saphenous vein was 7.9 ± 2.7 mm. There was no significant difference between left and right legs (right: 7.9±2.8 mm, left: 8.0±3.0 mm, P=0.95). The mean COL was 34.2 ± 1.9 mm, and there was a moderate positive correlation (r = 0.45). Conclusion: This study revealed that the saphenous nerve is running in parallel of the greater saphenous vein which can be depicted by the Vein Viewer Flex®. Ultrasonography after depicting greater saphenous vein enabled to confirm the saphenous nerve with certainly and noninvasive. These findings suggested that the combination of the Vein Viewer Flex® and ultrasonography enables the saphenous nerve block to be more reliable procedure even the saphenous nerve is hardly identified by the ultrasonography.